Bayesian Estimation of Individual Gray Whale Space Use Reveals Differential Exposure to Stressors - Lisa Hildebrand; Leslie New; Enrico Pirotta; Joshua D. Stewart; Ines Hildebrand; Carrie Newell; K. C. Bierlich; Clara N. Bird; Alejandro Fernandez Ajó; Daniel Turek; Leigh G. Torres (Ecology and Evolution)
ABSTRACT This study quantifies the individual space use patterns of Pacific Coast Feeding Group gray whales (Eschrichtius robustus) from photographic capture‐recapture data, collected in central Oregon, U.S.A., within a Bayesian framework. We evaluate the potential exposure of individuals to six anthropogenic stressors given their space use patterns. We used an 8‐year dataset of spatially explicit encounter histories collected via photo‐identification during continuous boat surveys to inform a Bayesian spatially explicit capture‐recapture model and estimate space use of individual whales. Space use estimates were combined with exposure values of four static (distance from two ports, distance from an effluent discharge site, area of whale watching) and two dynamic (commercial Dungeness crab pots, recreational fishing) anthropogenic stressors or their proxies to estimate relative individual stressor exposure. The influence of age and sex on space use patterns and stressor exposure was assessed post hoc. Space use, and thereby stressor exposure, was highly variable among individuals, both within and between years. Some individuals displayed remarkable long‐term and fine‐spatial‐scale site fidelity, not typically documented for large baleen whales. Juveniles concentrate their space use in a distinct area that is proximal to a port and center of whale watch activity. Exposure to stressors is highly variable across individuals and years given the heterogeneity of individual space use within the population and of stressor distribution, underscoring the complexity of managing wildlife populations. While population management plans need to be implemented at a population level, the recognition and incorporation of intraspecific variation can improve regulation efficacy since individual performance has relevant consequences on population health.